Serum and cerebrospinal fluid biomarker profiles in acute SARS-CoV-2-associated neurological syndromes. Issue 3 (12th May 2021) - Paterson, Ross W; Benjamin, Laura A; Mehta, Puja R; Brown, Rachel L; Athauda, Dilan; Ashton, Nicholas J; Leckey, Claire A; Ziff, Oliver J; Heaney, Judith; Heslegrave, Amanda J; Benedet, Andrea L; Blennow, Kaj; et al.
Abstract: Preliminary pathological and biomarker data suggest that SARS-CoV-2 infection can damage the nervous system. To understand what, where and how damage occurs, we collected serum and CSF from patients with COVID-19 and characterized neurological syndromes involving the PNS and CNS ( n  = 34). We measured biomarkers of neuronal damage and neuroinflammation, and compared these with non-neurological control groups, which included patients with ( n  = 94) and without ( n  = 24) COVID-19. We detected increased concentrations of neurofilament light, a dynamic biomarker of neuronal damage, in the CSF of those with CNS inflammation (encephalitis and acute disseminated encephalomyelitis) [14 800 pg/ml (400, 32 400)], compared to those with encephalopathy [1410 pg/ml (756, 1446)], peripheral syndromes (Guillain–Barré syndrome) [740 pg/ml (507, 881)] and controls [872 pg/ml (654, 1200)]. Serum neurofilament light levels were elevated across patients hospitalized with COVID-19, irrespective of neurological manifestations. There was not the usual close correlation between CSF and serum neurofilament light, suggesting serum neurofilament light elevation in the non-neurological patients may reflect peripheral nerve damage in response to severe illness. We did not find significantly elevated levels of serum neurofilament light in community cases of COVID-19 arguing against significant neurological damage. Glial fibrillary acidic protein, a marker of astrocytic activation, was not elevated in the CSF or serum of any group, suggesting astrocytic activation is not a major mediator of neuronal damage in COVID-19. Abstract : Paterson, Benjamin et al. report elevation of CSF neurofilament light (NfL), reflecting CNS damage, in some but not all SARS-CoV-2 associated neurological syndromes. Increased NfL concentration was a common finding in hospitalized patients with COVID-19, likely predominantly reflecting peripheral neuronal damage. Non-hospitalized individuals did not have elevated NfL. Graphical Abstract: